Intelligence and Security Informatics : Pacific Asia Workshop, PAISI 2015, Ho Chi Minh City, Vietnam, May 19, 2015. Proceedings - Chau, Michael; Wang, G. Alan.; Chen, Hsinchun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2015, held in Ho Chi Minh City, Vietnam, in May 2015 in conjunction with PAKDD 2015, the 19th Pacific-Asia Conference on Knowledge Discovery and Data Mining. The 8 revised full papers presented were carefully reviewed and selected from numerous submissions. Topics of the workshop are information sharing and big data analytics, infrastructure protection and emergency responses, cybercrime and terrorism informatics and analytics, as well as enterprise risk management, IS security, and social media analytics. The papers present a significant view on regional data sets and case studies, including online social media and multimedia, fraud deception, and text mining.
Media Revealr: A Social Multimedia Monitoring and Intelligence System for Web Multimedia Verification -- Geotagging Social Media Content with a Refined Language Modelling Approach -- Predicting Vehicle Recalls with User-Generated Contents: A Text Mining Approach -- GCM: A Greedy-based Cross-Matching Algorithm for Identifying Users across Multiple Online Social Networks -- P2P Lending Fraud Detection: A Big Data Approach -- Drug Anti-forgery and Tracing System Based on Lightweight Asymmetric Identities -- Chinese Word POS Tagging with Markov Logic -- In Search of Plagiarism Behaviors: An Empirical Study of Online Reviews.
Keywords: Computer security; Information storage and retrieva; Computer Communication Networks; Data mining; Computer science; Systems and Data Security; Information Storage and Retrieval; Computer Communication Networks; Data Mining and Knowledge Discovery; Computers and Society; Information Systems Applications (incl. Internet).